Effects of cadherin mediated contact normalization on oncogenic Src kinase mediated gene expression and protein phosphorylation - Nicoletto, Rachel E.; Holdcraft, Cayla J.; Yin, Ariel C.; Retzbach, Edward P.; Sheehan, Stephanie A.; Greenspan, Amanda A.; Laugier, Christopher M.; Trama, Jason; Zhao, Caifeng; Zheng, Haiyan; Goldberg, Gary S. (Scientific reports, 2024)
Nontransformed cells form heterotypic cadherin junctions with adjacent transformed cells to inhibit tumor cell growth and motility. Transformed cells must override this form of growth control, called “contact normalization”, to invade and metastasize during cancer progression. Heterocellular cadherin junctions between transformed and nontransformed cells are needed for this process. However, specific mechanisms downstream of cadherin signaling have not been clearly elucidated. Here, we utilized a β-catenin reporter construct to determine if contact normalization affects Wnt signaling in transformed cells. β-catenin driven GFP expression in Src transformed mouse embryonic cells was decreased when cultured with cadherin competent nontransformed cells compared to transformed cells cultured with themselves, but not when cultured with cadherin deficient nontransformed cells. We also utilized a layered culture system to investigate the effects of oncogenic transformation and contact normalization on gene expression and oncogenic Src kinase mediated phosphorylation events. RNA-Seq analysis found that cadherin dependent contact normalization inhibited the expression of 22 transcripts that were induced by Src transformation, and increased the expression of 78 transcripts that were suppressed by Src transformation. Phosphoproteomic analysis of cells expressing a temperature sensitive Src kinase construct found that contact normalization decreased phosphorylation of 10 proteins on tyrosine residues that were phosphorylated within 1 h of Src kinase activation in transformed cells. Taken together, these results indicate that cadherin dependent contact normalization inhibits Wnt signaling to regulate oncogenic kinase activity and gene expression, particularly PDPN expression, in transformed cells in order to control tumor progression.